Analisis Kemampuan Menulis Teks Eksposisi Siswa Kelas VI SD Negeri 16 Buatan II - Tri Widya Ningsih (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Exposure writing is an important ability to teach students because it enables readers to gain a better understanding of the subject or event written. Exposition text is a type of text that presents a variety of information to readers. The aim of this study was to explain the student's ability to write exposure texts that meet average standards. The students involved in this research are class VI students at SDN 16 Artificial II. This type of research is quantitative. In this study, the sample totaled 27 people. The data collection method was used to gather the results of students of class VI SDN 16 Built II from the exposition text writing test and give an assessment score for students' answers. The results of the study showed that students in SDN16 BuiltII had excellent ability to write exposure text, with an average of 83 points. There were no students in the very low or very low groups, 14 students (52%) were in the middle group, 13 students (48%) was in the high group, and no students were in a very high group